The Relationship between the Level of Knowledge about Hypertension and Efforts to Prevent Hypertension Complications in the Elderly - Refansa Desfa Dinata; Abi Muhlisin (Indonesian Journal of Global Health Research, 2024)
Hypertension is one of the non-communicable diseases caused by multifactorial and is one of the causes of mortality in the world. Based on information from the Surakarta City Health Office in 2023, it was stated high blood pressure cases in Surakarta City touched 67.355 cases. The goal of this study is to ascertain how attempts to prevent hypertension issues in the elderly at the Gambirsari Health Center relate to the degree of knowledge on hypertension. This kind of study is quantitative with a correlative descriptive method through a cross sectional approach. The population in this study was all elderly with high blood pressure who visited the Gambirsari Health Center, while the study sample was collected using a simple random sampling technique totaling 87 people. Data collection will be carried out in August 2024. The data was analyzed using the chi square test. The finding of the chi square statistical test obtained a value of p = 0.000 (p value < 0.05) so that H0 was rejected. The study's conclusion is that there is a relationship between the level of knowledge about hypertension and efforts to prevent hypertension complications in the elderly at the Gambirsari Health Center. Therefore, The findings of this study can serve as a reference for future scholars with different methods and as a reference for health facilities in developing relevant programs for hypertension patients.